Oxford wordpower dictionary - Wehmeier, Sally, ....- (Oxford : Oxford university press, 1994)
Oxford wordpower dictionary for intermediate learners of English. This new dictionary is written by teachers with the needs of the intermediate student firmly in mind. It shows learners how words relate to each other, helps them to build their vocabulary, and enables them to write and speak English with confidence. An introduction to the essential English of the nineties: > clear simple definitions using core vocabulary > 30 000 examples showing words in use > illustrations throughout the text depicting over 650 items > 1500 note explaining difficulties and showing links and contrasts between words > easy-to-use study section showing how the dictionary can become a powerful learning-tool
Keywords: Engels -- Woordenboeken